Autologous Mesenchymal Stem Cell Transplantation in Multiple Sclerosis: A Meta-Analysis. (23rd December 2019) - Zhou, Yang; Zhang, Xin; Xue, Hang; Liu, Lingling; Zhu, Jie; Jin, Tao
Abstract : Multiple sclerosis (MS) is considered to be a central nervous system (CNS) chronic inflammatory demyelinating disease, affecting more than 2 million individuals worldwide. In this meta-analysis, we aimed to assess the safety and efficacy of autologous mesenchymal stem cells (aMSCs) in treating MS patients. The PubMed, Embase, Cochrane, Web of Science, and Clinical Trial databases were searched in September 2019. The analysis was conducted for three endpoints: transplant-related mortality (TRM), rate of disease progression, and no evidence of disease activity (NEDA) status. RevMan and the metaprop command of the meta package in R was used in assessing the efficacy and safety of aMSCs. Subgroup analyses were performed for exploration of heterogeneity regarding outcomes. Nine studies comprising 133 patients were included in the meta-analysis. The pooled estimate of TRM was 0% (95% confidence interval (CI) 0%–0.3%). The rate of progression was 16% at 6 months (95% CI 10%–27%) and 35% at 1 year (95% CI 27%–46%). Lower 6-month and 1-year progression rates were significantly associated with intrathecal injection (p = 0.02 ; p = 0.003 ). The pooled proportion of NEDA patients at 6 months was 72% (95% CI 58%–89%) and at 1 year was 62% (95% CI 42%–81%). Cell transplantation with aMSCs in MS patients is safe, with the largest benefit profile obtained in patients with aMSCs intrathecal injection.